Inovasi Pendidikan Fikih Sebagai Dasar Pembentukan Karakter Religius Anak Usia Dini - Hanafi, Anas Rangga Buana (AUD Cendekia: Journal of Islamic Early Childhood Education, 2024)
This study aims to analyze the form, impact, and context of fiqh learning innovation in shaping the religious character of early childhood students at RA Al-Hikmah, Medan City. Using a qualitative phenomenological approach, this research explores the experiences of teachers, children, and parents through in-depth interviews, participatory observation, and documentation of learning activities. The findings reveal that fiqh learning innovation at RA Al-Hikmah is developed through play-based learning, storytelling, and project-based learning approaches that integrate worship values into children’s daily activities. Teachers also utilize educational digital media and create a religious learning environment, such as a mini mushalla, to strengthen the habituation of spiritual values. These innovations have a significant impact on the development of children’s religious character across five main dimensions: discipline, responsibility, honesty, social awareness, and spiritual consciousness. Furthermore, parental involvement through the school-family integration program enhances the continuity of religious values at home. The study concludes that contextual, enjoyable, and developmentally appropriate fiqh learning can effectively bridge the normative teachings of Islam with the challenges of the digital era. These findings are expected to serve as both a conceptual and practical model for Islamic early childhood education institutions in developing holistic and adaptive fiqh learning aligned with modern educational needs.